2016
DOI: 10.1109/jsyst.2013.2297705
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Proxy Mobile IPv6 Handover

Abstract: As wireless technologies have been improving in recent years, a mobility management mechanism is required to provide seamless and ubiquitous mobility for end users who are roaming among points of attachment in wireless networks. Thus, Mobile IPv6 was developed by the Internet Engineering Task Force (IETF) to support the mobility service. However, Mobile IPv6 is unable to fulfill the requirements of real-time applications, such as video streaming service and voice over IP service, due to its high handover (HO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…As a result of this problem, a network-based protocol has been proposed. PMIPv6 consists of new components of local mobility anchor (LMA), mobile access gateway (MAG), and authentication, authorization, and accounting (AAA) server (Modares et al 2016). The LMA acts as a kind of home agent for the mobile node in the domain.…”
Section: Mobility Management In Pmipv6mentioning
confidence: 99%
“…As a result of this problem, a network-based protocol has been proposed. PMIPv6 consists of new components of local mobility anchor (LMA), mobile access gateway (MAG), and authentication, authorization, and accounting (AAA) server (Modares et al 2016). The LMA acts as a kind of home agent for the mobile node in the domain.…”
Section: Mobility Management In Pmipv6mentioning
confidence: 99%
“…However, they have not investigated the video quality performance during the handover process. The researchers of this [14] paper have explored an elucidated review of the handover procedure of PMIPv6 protocols, and suggested mechanisms accompanied by a discussion about their points of weakness. The comparison of efficiency of the existing schemes in terms of handover latency and packet loss is shown in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…However, PMIPv6 was developed mainly for the local mobility management, which does not support a global mobility management [ 15 , 23 , 24 ]. For instance, when some MNs support only MIPv6 and intend to use PMIPv6, the network infrastructure should provide MIPv6 functions to them.…”
Section: Related Workmentioning
confidence: 99%